Peran Perempuan Dalam Mempertahankan Identitas Adat di Kampung Naga Kabupaten Tasikmalaya - Nurohman, Taufik; Yuliawati, Fitriyani; Widiastuti, Wiwi (Faculty of Social and Political Science, Universitas Siliwangi, 2025)
This article will explain how the role of indigenous women in maintaining traditional identity, including values and traditions. Women in indigenous communities in Indonesia are very interesting to explain, one of which is about the role of women in maintaining traditional identity in their respective customary communities as applies to the indigenous people of Kampung Naga, Tasikmalaya Regency. Although the women of Kampung Naga live in a patriarchal culture, as is the case with the culture of indigenous peoples in West Java in general, Kampung Naga women play an important role in the existence of adat in Kampung Naga. In terms of revitalizing traditional values and behavior patterns, Kampung Naga women carry out their role in educating their offspring to always adhere to customary values, including in terms of the livelihood system, housing system and how to dress. In addition, the women of Kampung Naga also play an important role in every implementation of Hajat Sasih. In terms of revitalizing physical culture, indigenous women continue to carry out their daily lives by remaining obedient in the use of household tools inherited from their ancestors.